Figurative Language in Kamala Harris’s Victory as Vice President Election Speech on BBC News - Juanda, Juanda; Mulyaningsih, Mulyaningsih; Amalia, Fara Dela Tasya; Supriadi, Asep (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
Communication is an action using languages to express ideas and feelings with other people from all over the world. Even from language also has the same role of communication where from language, people can express ideas, feelings, and thoughts that exist in each individual. Communication can be through indirect interaction or direct interactions, one of which is through speech. Through speech, people can spread their thoughts, instill their influence, and even provide good and systematic thinking directions. People who make good speeches will be able to persuade their listeners to accept and obey the thoughts, messages and ideas or messages they convey In delivering a speech, usually use language that has more meaning than what the speaker actually said. It refers to figurative language. Thus, this research will analyze the victory speech of the election of Kamala Harris as Vice President of the United States of America which was broadcast on BBC News on November 8, 2020. This research, entitled “Figurative Language in Kamala Harris’s Victory as Vice President Election speech on BBC news” is aimed at analyzing the figurative language used in the speech. Retrieving data based on watching a video of the speech from the BBC news youtube channel. After taking the data and analyzing it using the figurative language theory based on the theory of (Perrine 1974) which has several types of figurative languages. However, in this study, the writer only conducted several types such as Hyperbole, Simile, Personification and Paradox. In conducting this research, a descriptive qualitative method was used. The results of the analysis are described descriptively with their connotative and denotative meanings. In this study, hyperbole is one type of figurative language that is often found in Kamala Harris’s speech Keywords: Figurative language, Language, Connotative, Denotative, Meaning